QUESTIONING STRATEGIES USED BY SIXTH SEMESTER STUDENTS IN MICROTEACHING CLASS - Fatikha Izzatil Fitria; Fitri Budi Suryani; Achmad Hilal Madjdi (STKIP Persada Khatulistiwa Sintang, 2026)
Higher Order Thinking Skills (HOTS) are crucial for developing students’ critical thinking and problem-solving abilities. Using questioning tactics in the classroom has been found to improve HOTS by encouraging students to think more deeply and more involved. Teachers need to know how to ask different kinds of questions to help students learn, especially in English classes. This study explores the use of questioning strategies by EFL student teachers in microteaching course at the English Education Department (EED) of a private university in Indonesia. This qualitative phenomenological study used audio visual material from microteaching video and structured interviews to collect the data. The results of the study reveals that the EFL students teachers used three types of questions, namely procedural, convergent, and divergent questions. Convergent questions are the most dominant, while divergent questions are the least frequently used. The convergent questions are more related to lower-order thinking skills (LOTS), meanwhile, divergent questions are related to higher-order thinking skills (HOTS). Therefore, it is recommended that teacher educators should provide more focused training for crafting and using higher-order questions. Additionally, integrating Bloom’s Taxonomy explicitly into lesson planning and reflective teaching practices can help student teachers align their questioning strategies with intended learning outcomes across cognitive domains.